Hubungan Bauran Pemasaran dengan Loyalitas Pasien: Literature Review: The Relationship Between Marketing Mix and Patient Loyalty: Literature Review - Dinis das Neves Soares de Sousa; Wahyu Sulistiadi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: This research explores the relationship between the marketing mix (7Ps) and patient loyalty in the context of healthcare, particularly in outpatient units of hospitals in Indonesia. A deep understanding of factors influencing patient loyalty provides valuable insights for healthcare service managers. Objective: The main objective of this study is to identify and analyze the relationship between marketing mix elements, including product, price, promotion, place, process, people, and physical evidence, with patient loyalty in the hospital environment. The research also aims to provide insights into key factors influencing patients' decisions to revisit healthcare services Method: Using a systematic review approach following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, the study conducted searches on Scopus and Google Scholar databases, considering articles published between 2018 and 2023. Twelve articles meeting inclusion criteria were identified and analyzed Result: Research findings indicate a positive correlation between specific elements of the marketing mix and patient loyalty, emphasizing their significance in influencing patients' decisions to reuse healthcare services. Key influencing factors include service performance, responsiveness, adherence to standard timelines, and advertising. Conclusion: The study confirms the importance of specific marketing mix elements in shaping patient loyalty in hospitals. Location, promotion, personnel, and physical evidence emerge as key elements for hospitals to focus on in enhancing patient loyalty. Practical recommendations are provided as guidance for hospital managers to improve these aspects and enhance the overall patient experience.